2017
DOI: 10.1007/s11695-017-2835-y
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison Between Staple-Line Oversewing Versus No Reinforcement During Laparoscopic Vertical Sleeve Gastrectomy

Abstract: Oversewing of the staple line during LSG is a nonexpansive and easy method to decrease the incidence and severity of the postoperative bleeding. However, it is time-consuming and should be performed by experienced surgeons to avoid the complications which may occur secondary to the seroserotomy suturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Taha et al suggested that staple-line reinforcement by hand-sewing may require additional operating time and that average surgical time is significantly shorter in patients who underwent LSG without oversewing of the staple line. 22 This aspect is also highlighted in the meta-analysis of Wang et al 14 The shorter surgical time detected in our series may be due to the fact that the introduction of the reinforced lines occurred when the learning curve of the surgical team had already been completed, adding enough experience to be able to decrease surgical time. Studies by Aggrwal et al and Sroka et al suggest that the diminished bleeding rate after oversewn LSG may be attributed to the learning curve effect and not only the efficacy and effectiveness of the method of reinforcing the stapling line.…”
Section: Discussionsupporting
confidence: 52%
“…Taha et al suggested that staple-line reinforcement by hand-sewing may require additional operating time and that average surgical time is significantly shorter in patients who underwent LSG without oversewing of the staple line. 22 This aspect is also highlighted in the meta-analysis of Wang et al 14 The shorter surgical time detected in our series may be due to the fact that the introduction of the reinforced lines occurred when the learning curve of the surgical team had already been completed, adding enough experience to be able to decrease surgical time. Studies by Aggrwal et al and Sroka et al suggest that the diminished bleeding rate after oversewn LSG may be attributed to the learning curve effect and not only the efficacy and effectiveness of the method of reinforcing the stapling line.…”
Section: Discussionsupporting
confidence: 52%
“…On this line, Gagner et al, in a powerful review on 88 papers, shows in the no reinforcement group an overall complication rate of 8.9%, and confirmed that buttressing LSG suture did not determine a statistical evidence on leaks [21]. Almost all device making for reinforcing determine generally a faster procedure compared with oversewing suture, that is suitable for experienced surgeons [22].…”
Section: Discussionmentioning
confidence: 99%
“…These results were reported in multiple randomized controlled trials which demonstrated that the staple-line reinforcement in LSG had benefits over the postoperative staple-line hemorrhage and leakage. [17][18][19][20][21] Aggrwal et al and Sroka et al suggested that the diminished bleeding rate after oversewed LSG may be attributed to the learning curve effect and not only the efficacy of oversewing. 18,20 Miller et al and Kasalicky et al stated that the low hemorrhage rate with the buttressing material usage could be related to the more compression during tissue excision.…”
Section: Discussionmentioning
confidence: 99%